2006
DOI: 10.1007/s11430-006-0311-y
|View full text |Cite
|
Sign up to set email alerts
|

Belowground carbon balance and carbon accumulation rate in the successional series of monsoon evergreen broad-leaved forest

Abstract: The balance, accumulation rate and temporal dynamics of belowground carbon in the successional series of monsoon evergreen broadleaved forest are obtained in this paper, based on long-term observations to the soil organic matter, input and standing biomass of litter and coarse woody debris, and dissolved organic carbon carried in the hydrological process of subtropical climax forest ecosystem-monsoon evergreen broad-leaved forest, and its two successional forests of natural restoration-coniferous and broad-lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
23
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 6 publications
0
23
0
1
Order By: Relevance
“…The increasing trend of soil carbon is not always represented in the entire forest chronosequence or at each depth. Zhou et al (2006) found that pioneer and transition forests had limited effects on SOC accumulation even if the aboveground biomass rapidly accumulates and reaches a high level. In the hilly Loess Plateau of China, Wang et al (2010) indicated that SOC contents are significant for different land covers in a semi-arid climate only at 5 cm soil surface depth.…”
Section: Introductionmentioning
confidence: 99%
“…The increasing trend of soil carbon is not always represented in the entire forest chronosequence or at each depth. Zhou et al (2006) found that pioneer and transition forests had limited effects on SOC accumulation even if the aboveground biomass rapidly accumulates and reaches a high level. In the hilly Loess Plateau of China, Wang et al (2010) indicated that SOC contents are significant for different land covers in a semi-arid climate only at 5 cm soil surface depth.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have revealed that pioneer and transition forests have limited effects on soil organic carbon (SOC) accumulation even if the aboveground biomass accumulates rapidly and has attained a high level (Richter et al, 1999;Paul et al, 2002;Hooker and Compton, 2003;Johnson et al, 2003;Zhou et al, 2006a;Don et al, 2009), especially for pine forests (Richter et al, 1999;Paul et al, 2002;Zhou et al, 2006a). On the contrary, other evidences showed that broadleaved forests or those with nitrogenfixing trees may allocate a higher fraction of NPP into soils (Paul et al, 2002;Resh et al, 2002;Mendoza-Vega et al, 2003;Bush, 2008;Kiser et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…20 α-Cyclohexyl-mandelic acid, a derivative of MA, also has been studied by extraction. 21 But a single chiral selector is generally used for the resolution of MA and its derivatives, the enantioselectivity of these selectors are somehow low. 21 Based on the previous works, this paper investigated the extractive resolution of racemic MA (Figure 1), through a BLM by the complex of D2EHPA and L-(-)-DBTA as the binary chiral carrier, and tried to obtain the optimal conditions of extractive resolution.…”
Section: Introductionmentioning
confidence: 99%